Contribution of instructional leadership and teacher work discipline to teacher performance - Febrianti, Helsi; Nellitawati; Rusdinal; Jasrial (Universitas Jambi, Indonesia, 2025)
This research aimed to obtain data and information about the contribution of instructional leadership to teacher performance, teacher work discipline to teacher performance, and the contribution of instructional leadership and teacher work discipline to teacher performance at Islamic state junior high school in Pariaman City. This research was quantitative and correlational with the associative type. The population was 116 civil servant teachers. The sample was determined using the Cochran formula with an error rate of 10%, and the stratified proportional random sampling technique was used to obtain 58 teachers. The research instrument was a questionnaire with five alternative answers. The data analysis technique used multiple linear regression tests processed in SPSS version 26. The data analysis showed a significant contribution of instructional leadership and teacher performance, between teacher work discipline and teacher performance, and between instructional leadership and teacher work discipline to teacher performance. Instructional leadership contributes significantly to teacher performance. The better the instructional leadership shown, the better the performance of Islamic state junior high school teachers in Pariaman City. Also, teacher work discipline contributes significantly to teacher performance. The better the teacher’s work discipline, the better the performance of Islamic state junior high school teachers.